Для школьников влияние шахматного образования на развитие творческих способностей и интеллекта (Journal of Universal Science Research, 2023)
One of the main tasks of modern schools is the development of children's creative potential and the formation of socially significant personal qualities. At school, they should not receive ready-made knowledge, but a model of adaptation to rapidly changing conditions. According to a number of psychological and pedagogical indicators, the chess game is an ideal explanatory model that allows students to form skills for successfully solving practice-oriented problems. Our research is devoted to revealing the didactic possibilities of this explanatory model, where the authors define approaches to the content interpretation and content of the concept of "didactic potential of chess", its essence and structure. The main attention is paid to the correlation of chess training and the dynamics of improving academic performance in other academic subjects. The comparative indicators of improving student's academic performance in the selected subjects with the growth of chess skills are presented on the example of subjects “Russian language and literature”, “Mathematics” and “Foreign (English) language”. In terms of didactics, methodology and technology, the thesis is substantiated that chess contributes to the development of logical, creative, critical and independent thinking of the student, which directly affects the success of learning in other academic subjects. The work is interdisciplinary in nature.